Drezotomia lumbosacra para control de dolor en niños con parálisis cerebral y luxación dolorosa de cadera. - Muñoz, Víctor Adrián; Bertolotti , R; Torresi , J; Martinez, S; Martinez, S; Borgino, V; Chinchallan , J (Revista Argentina de Neurocirugía, 2021)
In patients with Chronic Non-Evolutionary Encephalopathy (NECE) and disabling spasticity, painful hip dislocation is a common complication. For his treatment, many orthopedic techniques have been described. However, pain and spasticity continue to be present in a significant number of patients, despite a correct surgical correction. Microsurgical Drezotomy (DREZ) is a neurosurgical technique described for pain and spasticity treatment in adults. We describe our results obtained with this technique for hip dislocation pain treatment in children with disabling spasticity.